Pesan Anti Rasisme dalam Pertandingan Kualifikasi Euro 2020 Belanda vs Estonia di Mola TV - Fadhilah Nur Iman; Santi Delliana (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
antagonism towards many forms of racism. Instances of racial discrimination and prejudice are prevalent within the domain of football. A diverse range of individuals, including supporters, coaches, athletes, officials overseeing matches, and media members, are accountable for participating in racist practices. The establishment of the Let's Kick Racism Out of Football program by the Federation Internationale de Football Association (FIFA) was a direct response to the occurrence of racism within the football community. The primary aim of this research is to investigate the potential existence of an anti-racist message inside the live broadcast of the Netherlands vs Estonia match on Mola TV. The research methodology adopted in this study involves using a descriptive qualitative approach. The methodology utilized in this study is the semiotic approach. The methodology adopted for data analysis is grounded in the principles of semiotics as established by Charles S. Peirce. The theoretical framework utilized in this research is the constructivism paradigm. The present study utilizes the theoretical framework of Social Reality Construction in Mass Media. The results of this study unveiled several forms of anti-racism indicators, encompassing gestures involving bodily motions, observable characteristics, spatial clues, and temporal factors. The match's goal celebration sequences effectively convey an anti-racism tone through the presence of such messages.